Kinship Analysis with Diallelic SNPs - Experiences with the SNPforID Multiplex in an ISO17025 Accreditated Laboratory - Børsting, Claus (S. Karger GmbH, 2012)
BACKGROUND: The mutation rate of single nucleotide polymorphisms (SNPs) is estimated to be 100,000 times lower than that of short tandem repeats (STRs), which makes SNPs very suitable for relationship testing. The SNPforID multiplex assay was the first SNP typing assay that was a real alternative to the commonly used STR kits in kinship and crime case work and the first SNP assay to be validated in a forensic laboratory accredited according to the ISO17025 standard. METHODS: A total of 54 crime case samples were typed with the SNPforID multiplex assay. 30 samples from relationship cases were sequenced in selected SNP loci. RESULTS: It was demonstrated that mixtures were easily detected with the SNPforID assay by analyzing the signal strengths of the detected alleles. Unusual imbalances in signal strengths that were observed in a few individuals could be explained by unexpected SNPs in one of the primer binding sites. A complicated relationship case with four closely related individuals is presented. CONCLUSION: Mixtures can be detected with bi-allelic SNPs. The SNPforID assay is a very useful supplement to the STR kits in relationship testing.